ESTIMATION OF GENETIC DIVERGENCE IN SOME MID LATE AND LATE CAULIFLOWER ( ULIFLOWER (Brassica oleracea Brassica oleracea Brassica oleracea Var. botrytis . botrytis L.) GERMPLASM - SUBHRAJYOTI CHATTERJEE; SHWETA SHARMA; SUMIT PATIL, DEBMALA MUKHERJEE (The Bioscan, 2018)
The present investigation was undertaken at the Experimental Farm of the Department of Vegetable Science, Dr. YS Parmar University of Horticulture and Forestry, Solan, Himachal Pradesh during Rabi season of 2016 to estimate genetic divergence in twenty mid late and late germplasm of cauliflower for ten quantitative characters. The genotypes were grouped into four clusters. Cluster II was found to have maximum (8) number of genotypes while both Cluster I and III contained minimum (3) genotypes each. The genetic stocks within a cluster had smaller D2 values among themselves than those belonging to different clusters. Intra-cluster distance was maximum (2.091) in cluster IV whereas, it was minimum (1.086) in cluster I. Highest average inter-cluster distance (6.496) was recorded between cluster I and cluster IV. Cluster IV recorded highest mean value for most of the characters. Considering the diversity pattern and mean performances, the genotypes namely EC-683461 from cluster I, SelI from cluster II, Kt-25 from cluster III and Hermia, Sel-II, Pant Shubhra from cluster IV would be best choice as parents for future hybridization programme.